2012
DOI: 10.1002/jqs.1563
|View full text |Cite
|
Sign up to set email alerts
|

Variation and pattern in the responses of mammal faunas to Late Pleistocene climatic change in southeastern South Australia

Abstract: We examined mammal occurrence and variability through the Late Pleistocene vertebrate fossil deposit of Grant Hall in Victoria Fossil Cave, Naracoorte, South Australia. To determine long‐term patterns of change, we compared the composition and relative abundance trends of the assemblage with a nearby Middle Pleistocene deposit in Cathedral Cave. Total species richness did not change through the Grant Hall sequence, dated from 93 ± 8 to 70 ± 5 ka. However, species relative abundances varied between ecologically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…1 and Sminthopsis sp. 1; Appendix) were common in the late Quaternary aged assemblages examined here but have not been noted in older fossil assemblages (Reed & bourne 2000;Prideaux et al 2007;macken et al 2012). two species previously listed for Wet Cave and RCiC respectively, Cercartetus concinnus and Petauroides volans, were not identified in the current re-examination of these fossil collections.…”
Section: Diversitymentioning
confidence: 50%
See 4 more Smart Citations
“…1 and Sminthopsis sp. 1; Appendix) were common in the late Quaternary aged assemblages examined here but have not been noted in older fossil assemblages (Reed & bourne 2000;Prideaux et al 2007;macken et al 2012). two species previously listed for Wet Cave and RCiC respectively, Cercartetus concinnus and Petauroides volans, were not identified in the current re-examination of these fossil collections.…”
Section: Diversitymentioning
confidence: 50%
“…three species (Antechinus minimus, A. stuartii and A. swainsonii) were not identified in the studied assemblages but are present in assemblages of the nCWhA dated older than c. 70 ka (Smith 1972;Reed & bourne 2000;Prideaux et al 2007;macken et al 2012). Reed and bourne (2000) suggested that identification of Antechinus species from nCWhA deposits may require revision, particularly as A. minimus, A. stuartii and A. swainsonii were only known from single deposits at the time of their publication.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations